2018
DOI: 10.3389/fonc.2018.00301
|View full text |Cite
|
Sign up to set email alerts
|

BCMA (TNFRSF17) Induces APRIL and BAFF Mediated Breast Cancer Cell Stemness

Abstract: Recent advances in cancer immunology revealed immune-related properties of cancer cells as novel promising therapeutic targets. The two TNF superfamily members, APRIL (TNFSF13), and BAFF (TNFSF13B), which are type II membrane proteins, released in active forms by proteolytic cleavage and are primarily involved in B-lymphocyte maturation, have also been associated with tumor growth and aggressiveness in several solid tumors, including breast cancer. In the present work we studied the effect of APRIL and BAFF on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…This was further supported by the preferential expression of APRIL and its receptors in a small series of triple-negative human tumors as compared to luminal-type carcinomas (149). Finally, the authors reported a direct effect of APRIL on cell proliferation [reported also by other groups (150,151)] and the induction of tumor xenografts in an APRIL-rich environment. Interestingly, in a recent work (151), we have reported that APRIL is upregulated by membrane-acting androgen, and that induces breast cancer cell migration and epithelial-to-mesenchymal transition, together with mammosphere formation and induction of stemness.…”
Section: April-baff System In the Breastmentioning
confidence: 52%
“…This was further supported by the preferential expression of APRIL and its receptors in a small series of triple-negative human tumors as compared to luminal-type carcinomas (149). Finally, the authors reported a direct effect of APRIL on cell proliferation [reported also by other groups (150,151)] and the induction of tumor xenografts in an APRIL-rich environment. Interestingly, in a recent work (151), we have reported that APRIL is upregulated by membrane-acting androgen, and that induces breast cancer cell migration and epithelial-to-mesenchymal transition, together with mammosphere formation and induction of stemness.…”
Section: April-baff System In the Breastmentioning
confidence: 52%
“…Previous work suggests that FAM171 A1 may be associated with chemoresistance of cancer cells 2,3 . Data-mining studies suggest that FAM171A1 interacts with FAM171B, PCDHGB1, TNFRSF17, TMEM, CTDSPL, and NTRK1 47 , many of which have been implicated in various cancers 813 . Emerging reports suggest that FAM171A1 might be overexpressed in TNBC tumors 1416 .…”
Section: Introductionmentioning
confidence: 99%
“…The peroxisome proliferator-activated receptor-γ coactivator 1-α (PPARGC1A) gene also contributes to tumor growth and metastasis in several cancers [ 68 , 69 ]. In addition, studies have suggested that both the paired related homeobox 2 (PRRX2) gene [ 70 , 71 ] and the tumor necrosis factor receptor superfamily member 17 (TNFRSF17) gene [ 72 , 73 ] are associated with the development of several cancers, while the proprotein convertase subtilisin/kexin type 5 (PCSK5) gene and the WD repeat domain 78 (WDR78) gene have not been reported to be associated with pathogenesis and progression. Thus, the functions of these genes in colon cancer should be further investigated using preclinical and clinical experiments.…”
Section: Discussionmentioning
confidence: 99%